1998
DOI: 10.1113/expphysiol.1998.sp004094
|View full text |Cite
|
Sign up to set email alerts
|

Changes in skeletal muscle sarcoplasmic reticulum function and force production following myocardial infarction in rats

Abstract: SUMMARYIn patients following myocardial infarction (MI), exercise tolerance and muscular strength are often markedly reduced. The purpose of this investigation was to determine if calcium (Ca2+) uptake and release by skeletal muscle sarcoplasmic reticulum (SR) are altered following MI and if such changes are associated with diminished muscular performance. SR vesicles were isolated from rat gastrocnemius muscle at 6 and 12 weeks following MI (via left coronary artery ligation) or sham surgery. At both post-sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
16
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 28 publications
3
16
1
Order By: Relevance
“…If the increased fragility during microdissection that we observed is taken into account, it is possible that recovery after the macroinjection of aequorin was markedly impaired preferentially in muscles from CHF rats. This would also explain the apparent conflict between the large effects on contractile function observed in the study of Perreault et al and the modest changes in contractile function and protein expression observed with similar models of CHF in the present and other 7,10 studies. An alternative explanation might be that the isolated single fibers used in the present study are not representative of the whole muscle; eg, it could be that the fibers that contracted after dissection were the only fibers with almost unaltered properties.…”
Section: Lunde Et Alcontrasting
confidence: 53%
See 1 more Smart Citation
“…If the increased fragility during microdissection that we observed is taken into account, it is possible that recovery after the macroinjection of aequorin was markedly impaired preferentially in muscles from CHF rats. This would also explain the apparent conflict between the large effects on contractile function observed in the study of Perreault et al and the modest changes in contractile function and protein expression observed with similar models of CHF in the present and other 7,10 studies. An alternative explanation might be that the isolated single fibers used in the present study are not representative of the whole muscle; eg, it could be that the fibers that contracted after dissection were the only fibers with almost unaltered properties.…”
Section: Lunde Et Alcontrasting
confidence: 53%
“…In accordance, a more recent study showed more moderate and, in some instances, apparently opposite changes in contractile function and Ca 2ϩ handling in skeletal muscle from rats with myocardial infarction. 10 Having this in mind, we compared contractile function, intracellular Ca 2ϩ handling, and fatigue resistance of intact, single, fast-twitch muscle fibers from CHF and sham-operated rats (CHF and sham fibers, respectively). The results show no major changes in the contractile function and Ca 2ϩ handling of unfatigued fibers from CHF rats.…”
mentioning
confidence: 99%
“…Interestingly, and in contrast to the slowed muscle contraction and relaxation rates, there was a tendency toward increased SR Ca 2ϩ release and uptake in CHF compared with Sham. This is in agreement with previous studies showing accelerated SR Ca 2ϩ uptake and release at 37°C in fast-twitch and mixed muscle from rats with moderate heart failure (32,44). One could speculate that the accelerated SR Ca 2ϩ cycling reflects an attempt by the muscle to compensate for slowed kinetics of the contractile machinery in skeletal muscle during CHF.…”
supporting
confidence: 81%
“…However, it is also possible that changes in skeletal muscles associated with heart failure contributed to the progressive decline in exercise capacity in our rats. Specifically, it has also been shown that skeletal muscles become progressively weaker with heart failure (4), due to changes in calcium handling and force production of myocytes (24), and also due to skeletal muscle cell atrophy (10,15) and apoptosis (14). Related to these changes in skeletal muscle are alterations in blood flow to the periphery.…”
Section: Discussionmentioning
confidence: 99%